Horizontal and vertical dimensions of visual extinction: a theta burst stimulation study. - Cazzoli, D; Müri, R; Hess, C; Nyffeler, T (2009)
After a lesion of the posterior parietal cortex (PPC), the perception of a contra-lesional stimulus in presence of a simultaneous, ipsilesional stimulus may be impaired, a phenomenon referred to as visual extinction. In the present study, visual extinction was transiently induced in healthy subjects by interfering with the function of the right PPC by means of continuous theta burst stimulation (TBS). We investigated to which extent the horizontal and vertical position of visual stimuli influenced the extinction rate. A single TBS train over the right PPC induced a significant increase of left visual extinctions of at least 30 min. Left visual extinction rate was higher when the left sided visual stimulus was presented at a more eccentric position on the horizontal axis (irrespective of right sided visual stimulus position) and in the lower part of the visual field. The results are discussed within the framework of current explanatory models and of putative inter- and intrahemispheric mechanisms directing visuospatial attention.